2007
DOI: 10.1111/j.1745-4557.2007.00141.x
|View full text |Cite
|
Sign up to set email alerts
|

CHANGES IN APPARENT VISCOSITY AND VITAMIN C RETENTION DURING THERMAL TREATMENT OF BUTTERNUT SQUASH (CUCURBITA MOSCHATA DUCH) PULP: EFFECT OF RIPENING STAGE

Abstract: The effects that ripening stage have on the apparent viscosity and ascorbic acid retention in squash pulp exposed at cooking process were analyzed. Total soluble solids contents were taken as indicative of ripening degree. In the raw material, water contents ranged from 79 to 96%, but no significant differences were observed among samples grouped as unripe, ripe and overripe. The ascorbic acid contents of pulp increase with increases in soluble solids contents. Pulp from unripe and ripe squash had similar ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
4
9
1
Order By: Relevance
“…While Edwa and Kafr-El-Batikh cultivars recorded low values (2.30 and 3.90 mg/100g, respectively). The high values of vitamin C in Qina and Kafr-Saad cultivars were similar that reported by Walker (1978) and Roura et al (2007) who found that vitamin C in pumpkin was 30 and 22.87 mg/100g, respectively. While the low values of Edwa and Kafr-El-Batikh cultivars were agreement with the results of Sudhakar et al (2003) and Marina et al (2009).…”
Section: Minerals Contentsupporting
confidence: 89%
“…While Edwa and Kafr-El-Batikh cultivars recorded low values (2.30 and 3.90 mg/100g, respectively). The high values of vitamin C in Qina and Kafr-Saad cultivars were similar that reported by Walker (1978) and Roura et al (2007) who found that vitamin C in pumpkin was 30 and 22.87 mg/100g, respectively. While the low values of Edwa and Kafr-El-Batikh cultivars were agreement with the results of Sudhakar et al (2003) and Marina et al (2009).…”
Section: Minerals Contentsupporting
confidence: 89%
“…Tamer et al (2010) reported lower values of L* (49.6) and higher values in a* (21.9) and b* (31.0). Soluble solids determined in the present experimental work were lower than the reported by Roura et al (2007) and Noseworthy and Loy (2008) (8-11 and 7.0-8.7 °Brix, respectively) for C. moschata. The pH values were higher than the reported by Tamer et al (2010) (5.80) in C. moschata.…”
Section: Physicochemical Characterizationcontrasting
confidence: 78%
“…Because the preparation and stabilization of home-cooked products, such as soups and sauces from squash pulp, would involve thermal treatments, the ascorbic acid retention in squash pulp held for 30 min at 95 o C was investigated. The percentage of ascorbic acid retention was 82.43 + 2% (Roura et al, 2007). On the basis of our results there can be confi rmed conservation of vitamin C, providing the thermal treatment -baking, only on 61% in average in case of all observed varieties (Tab.…”
Section: Evaluation Of Vitamin C Contentmentioning
confidence: 71%